The Global Prevalence of Iron Deficiency in Collegiate Athletes: A Systematic Review and Meta‐Analysis - Thompson, Christineil; Block, Darci; Wang, Zhen; Foster, Nathan; Hassett, Leslie C.; Steien, Dana; Galardy, Paul; Al‐Huniti, Ahmad (Pediatric blood & cancer, 2025)
ABSTRACT Athletes are at high risk of iron deficiency even without anemia. In this systematic review and meta‐analysis that included 17,519 athletes in 122 references from 23 countries, participating in 62 unique sports over a 41‐year timeframe, approximately 53.9% of student‐athletes were found to be hypoferritinemic (ferritin concentration below 50 mcg/L) with 23.0% percent showing absolute iron deficiency based on current definitions (ferritin concentration below 20 mcg/L). These findings strongly suggest that changes in clinical practice guidelines are warranted to enable routine screening for iron deficiency among adolescent and collegiate athletes.